SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER - Indah - Widiastuti (STIE AUB Surakarta, 2015)
In order to provide a quick, precise, and accurate financial report, it takes an accounting information System. Accounting Information System can be done both in manual or in computerization. Nowdays, most company are leaving the manuals Accounting Information System, and turning into computerized Accounting Information System. These research is a literatur review about the role, obstacles, and solution of Computerized Accounting Information System. The Existence of Computerized Accounting Information System can provide many benefits and an important role for the company in achieving the objectives effectively and efficiently. However , the company also have to solve the problems that hinder the success of computer-based accounting information system related to human resources and maintenance of computer-based accounting information system itself. Equipping human resources with expertise in accounting / finance and skills in computer technology, and always maintain recency software and hardware computer-based accounting information system to be conducted by the company so that the system can run optimally. Keywords : information system, Accounting Information System, Computerized Accounting Information System.